The effects of exercise intensity on blood markers of oxidative stress in recreational male athletes - Yan, Wong Yee (Universiti Sains Malaysia, 2013)
The purpose of this study is to investigate the acute effect of 30 minutes exercise at 50-60% and 80-90% of maximum heart rate on blood oxidative stress markers in recreational male athletes. Thirteen male recreational athletes (age: 21.8 ± 1.5 years old; body weight: 64 ± 8.5 kg; height: 170.6 ± 7.3cm) from Health Campus of Universiti Sains Malaysia participated in this study. This was a randomized cross-over study. Subjects were required to perform two trials with a break of week, low (50-60% of MHR) VS high intensity (80-90% of MHR) exercise for 30 minutes. Heart rate and the rate of perceived exertion (RPE Borg’s Scale) were measured at an interval of 5 minutes. Blood samples were drawn at pre-exercise, postexercise and 24 hours post-exercise. The blood samples were analysed for haematocrit level, lipid peroxidation, total antioxidant power, reduced glutathione (GSH), oxidized glutathione (GSSG) and GSH:GSSG ratio. Two way ANOVA with repeated measures was used to determine the differences between trials and changes of the measured parameters over time. The results showed there was no significant difference in the changes of oxidative stress markers between low and high intensity exercise. However, exercise at high intensity (80- 90% MHR) showed a trend of higher oxidative stress markers levels than low intensity exercise (50-60% MHR). In addition, there were also no significant differences between trials in plasma volume changes between low and high exercise intensity workout for 30 minutes. In conclusion, these data demonstrated that 30 minutes of exercise at low and high intensity did not have statistically significant difference in oxidative stress markers’ level.